Flux and solder paste containing flux
The solder paste with a specialized flux formulation addresses defects in solder joints by minimizing air content, ensuring robust connections and effective soldering without inert gas, enhancing soldering efficiency and quality.
Patent Information
- Application Number
- JP2024109274
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-07-20
- Filing Date
- 2024-07-06
- Publication Date
- 2025-01-30
- Estimated Expiration
- 2044-07-06
AI Technical Summary
Existing solder pastes often result in defective solder joints due to high gas or air content, requiring inert gas environments to mitigate air oxidation, which complicates the soldering process.
A solder paste containing a flux composed of 30-80% acidic resin, 10-60% organic solvent, and optional 0-15% amine, with specific weight average molecular weights and acid values, designed to minimize air content and enhance soldering properties without requiring inert gas environments.
The flux formulation reduces defects in solder joints by minimizing air content, ensuring strong connections and effective soldering without the need for inert gas, while maintaining excellent soldering properties.
Smart Images

Figure 2025015455000001
Abstract
Description
[Technical field]
[0001] The present invention relates to fluxes for solder pastes, and in particular to solder pastes containing fluxes for attaching electronic components to substrates.
[0002] Solder pastes, in particular soft solder pastes, are primarily used in the manufacture of electronic circuits to create mechanical, electrical and thermal connections between electronic components and substrates, or more precisely between the contact surfaces of the latter provided for this purpose. Summary of the Invention [Problem to be solved by the invention]
[0003] Examples of electronic components within the meaning of this patent application include diodes, LEDs (light emitting diodes), dies, IGBTs (insulated gate bipolar transistors), MOSFETs (metal oxide semiconductor field effect transistors), ICs (integrated circuits), sensors, heat sinks, resistors, capacitors, coils, connecting elements (e.g. clips), base plates, antennas, etc.
[0004] Examples of substrates within the meaning of this patent application include lead frames, PCBs (printed circuit boards), flexible electronics, ceramic substrates, ceramic metal substrates such as DCB substrates (direct bond copper substrates), IMS (insulated metal substrates), etc.
[0005] Electronic components are typically contacted or applied to a substrate via a solder paste. The solder paste is heated to melt the solder (solder metal, solder alloy) in the paste, for example by a reflow process. After the solder cools and solidifies, the electronic component and substrate are firmly joined together.
[0006] In addition to the solder powder, solder pastes typically contain a flux, which serves, among other things, to dissolve oxide layers on the surfaces of the solder powder, electronic components and substrates, thereby improving wettability during the soldering process.
[0007] Fluxes forming part of the solder pastes are typically based on natural resins, in particular colophony, and furthermore organic solvents, buffer bases, e.g. amines, and activators, e.g. carboxylic acids or halogen compounds, are typically included as ingredients in such fluxes.
[0008] The object of the present invention is to provide a solder paste with as low as possible defects in the form of voids, e.g. gas or air content, in the solder joints produced from the solder paste. The solder paste to be found should also have good solderability in the presence of air, i.e. without the need to take special measures to exclude atmospheric oxygen, such as vacuum soldering or soldering under inert gas.
[0009] The applicant has been able to develop a flux that solves this problem, or more precisely a solder paste that includes a flux that solves this problem. The present invention therefore relates to a flux comprising: (i) 30 to 80% by weight (wt%), preferably 40 to 70% by weight, of one or more acidic resins; (ii) 10 to 60% by weight, preferably 20 to 50% by weight, of at least one organic solvent; (iii) 0 to 15% by weight, preferably 4 to 12% by weight, of one or more amines; (iv) 0 to 20% by weight of one or more components other than components (i) to (iii); The object of the present invention is to provide a flux characterized in that during a thermogravimetric analysis (TGA) carried out in the range of 25-350°C with the addition of synthetic air at a heating rate of 10 K / min, it undergoes a weight loss of ≥ 50% by weight when a temperature of 280°C is reached.
[0010] Depending on the presence of components (iii) and / or (iv), the flux according to the present invention may accordingly consist of components (i)+(ii), or (i)+(ii)+(iii), or (i)+(ii)+(iv), or (i)+(ii)+(iii)+(iv), in each of these alternatives the sum of the weight percent of the respective components equals 100 weight percent.
[0011] The flux according to the invention comprises as component (i) 30-80% by weight, preferably 40-70% by weight, of one or more acidic resins. The one or more acidic resins may be selected from the group consisting of acidic oligoesters and acidic (meth)acrylic copolymers. "(Meth)acrylic" means "methacrylic" and / or "acrylic". The acidic oligoesters and the acidic (meth)acrylic copolymers are each in particular carboxyl group-containing resins, i.e. resins which owe their acidic properties to their carboxyl groups.
[0012] In a first embodiment, component (i) of the flux according to the invention consists of one or more acidic resins in the form of one or more different acidic oligoesters.
[0013] In a second embodiment, component (i) of the flux according to the invention consists of one or more acidic resins in the form of one or more different acidic (meth)acrylic copolymers.
[0014] In a third embodiment, component (i) of the flux according to the present invention consists of a combination of one or more acidic oligoesters and one or more acidic (meth)acrylic copolymers.
[0015] The acid oligoesters referred to herein as possible components (i) have an acid number in the range of 150 to 300 mg KOH / g and a weight average molecular weight M in the range of 300 to 600. w It has an acid value in the range of 200 to 250 mg KOH / g and a weight average molecular weight M in the range of 400 to 550. wParticularly preferred is an acid oligoester having an acid number in the range of 200 to 250 mg KOH / g and a weight average molecular weight M in the range of 400 to 550. w In the present specification, a distinction is made between one acid oligoester and several different acid oligoesters. To avoid any doubt, the term "acid oligoester" refers to a mixture of oligomers or oligomeric polyesters having a qualitatively and quantitatively defined structure, i.e., a structure consisting of building blocks defined by type and amount. The weight average molecular weight M w As already seen from the above, the "acid oligoesters" also have a molecular weight distribution, i.e. they exist as a mixture of oligomeric polyester molecules of different sizes. Thus, the term "several different acid oligoesters" refers to a combination of different oligomer mixtures or to several oligomeric polyesters of different structures, each of which has a molar mass distribution.
[0016] The term "acid number" as used in the specification and examples refers to the acid number (SZ) which can be determined in accordance with DIN EN ISO 2114 in mg KOH / g (milligrams KOH / gram).
[0017] Unless otherwise noted, all standards cited herein are the editions prevalent as of the priority date of this patent application.
[0018] The weight average molecular weight M referred to in the specification and examples w can be determined in the usual manner known to those skilled in the art by GPC, for example according to DIN 55672-1 (March 2016; crosslinked polystyrene as stationary phase, tetrahydrofuran as liquid phase, polystyrene standards, 23° C.).
[0019] The acidic oligoesters can be composed of one or more different low molecular weight polyols as the hydroxyl building blocks and one or more different low molecular weight polycarboxylic acids as the carboxyl building blocks.
[0020] The term "low molecular weight" as used herein refers to compounds that do not have a molar mass distribution defined by their molecular and structural formula.
[0021] The acid oligoester is preferably a linear acid oligoester having one or two terminal carboxyl groups, or a mixture of such oligoesters. A preferred linear acid oligoester can be composed of one or more different low molecular weight diols and one or more different low molecular weight dicarboxylic acids. Examples of low molecular weight diols include aliphatic and cycloaliphatic diols, such as ethylene glycol, 2-ethyl-1,3-hexanediol, 1,2- and 1,3-propylene glycol, 1,3-butanediol, 1,4-butanediol, 2,3-butanediol, 1,5-pentanediol, 1,6-hexanediol, trimethylhexanediol, hydrogenated bisphenols, cyclohexanediol, 1,4-cyclohexanedimethanol, neopentyl glycol and butylethylpropanediol. Preferably, the low molecular weight diol is selected from the group consisting of low molecular weight cycloaliphatic diols. Low molecular weight dicarboxylic acids include, for example, tetrahydrophthalic acid, maleic acid, fumaric acid, hexahydrophthalic acid, 1,3-cyclohexanedicarboxylic acid and 1,4-cyclohexanedicarboxylic acid, adipic acid, malonic acid, succinic acid, glutaric acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, undecanedioic acid, dodecanedioic acid, and tridecanedioic acid. Preferably, the dicarboxylic acid is selected from the group consisting of aromatic dicarboxylic acids, such as the isomeric phthalic acids, especially orthophthalic acid.
[0022] The method of preparing acidic oligoesters by polycondensation of low molecular weight polyols as hydroxyl building blocks and low molecular weight polycarboxylic acids as carboxyl building blocks is well known to those skilled in the art, i.e. synthetic resin chemists or polymer chemists. In polycondensation, which is typically carried out in the melt, water is separated during the esterification reaction, and is removed from the reaction mixture, in particular by distillation, sometimes azeotropically, or supported by applying a vacuum. Of course, instead of polycarboxylic acids (if available), the corresponding acid anhydrides can be used, which can be esterified with hydroxyl building blocks by ring opening.
[0023] The acidic (meth)acrylic copolymers referred to in this specification as possible components (i) have an acid number in the range of 100 to 350 mg KOH / g, preferably 150 to 300 mg KOH / g. Preferably, this concerns only one such acidic (meth)acrylic copolymer. The acidic (meth)acrylic copolymer has, for example, a weight average molecular weight M in the range of 1000 to 3500, or preferably in the range of 1000 to 3000. w It has an acid value in the range of 100 to 350 mg KOH / g and a weight average molecular weight M in the range of 1000 to 3500. w The preferred is an acidic (meth)acrylic copolymer having an acid value in the range of 150 to 300 mg KOH / g and a weight average molecular weight M in the range of 1000 to 3000. wParticularly preferred are acidic (meth)acrylic copolymers having the formula: These are copolymers of (meth)acrylic compounds that can be prepared in the usual manner known to those skilled in the art by radical copolymerization, and it is also possible for the copolymers to contain comonomers other than (meth)acrylic type comonomers, such as vinyl compounds and / or other olefinically unsaturated radically copolymerizable compounds, in a total weight percentage of <50% by weight, based on the total acidic (meth)acrylic copolymer. Examples of (meth)acrylic compounds that constitute >50% by weight, based on the total (meth)acrylic copolymer, are (meth)acrylic acid, (meth)acrylic acid esters and (meth)acrylamides. Examples of vinyl compounds include compounds such as vinyl esters, vinyl ethers, styrene, etc.
[0024] The acidic (meth)acrylic copolymer has a glass transition temperature (T) in the range of >0°C but generally ≦105°C. g The glass transition temperature can be determined using differential scanning calorimetry (DSC) according to DIN 51007 at a heating rate of 10 K / min.
[0025] Acidic (meth)acrylic copolymers of the type described above are commercially available, examples of which include products under the name Indurez from Indulor Chemie GmbH and products under the name Joncryl® from BASF.
[0026] As component (ii), the flux according to the invention comprises 10-60% by weight, preferably 20-50% by weight, of at least one organic solvent. Examples include diols, alcohols, ether alcohols, and ketones that are liquid at 25°C, in particular trimethylpropanol, 1,2-octanediol, 1,8-octanediol, 2,5-dimethyl-2,5-hexanediol, isobornylcyclohexanol, glycol ethers, 2-ethyl-1,3-hexanediol, n-decyl alcohol, 2-methyl-2,4-pentanediol, terpineol, and isopropanol, as well as mixtures thereof. Examples of glycol ethers include mono-, di-, and tripropylene glycol methyl ether, mono-, di-, and tripropylene glycol n-butyl ether, mono-, di-, and triethylene glycol n-butyl ether, ethylene glycol dimethyl ether, triethylene glycol methyl ether, diethylene glycol dibutyl ether, tetraethylene glycol dimethyl ether, and diethylene glycol monohexyl ether, as well as mixtures thereof. For the avoidance of doubt, the diols given as examples herein relate to diols that are intentionally added as type (ii) components when formulating the flux according to the invention, and should not be confused with any unintentional and unavoidable impurities in the flux according to the invention in the form of trace amounts of diols that are used as hydroxyl building blocks in the synthesis of any acidic oligoesters and that are not incorporated (condensed) into the acidic oligoesters.
[0027] As component (iii), the flux according to the present invention comprises 0-15 wt. %, preferably 4-12 wt. %, of one or more amines, i.e. the flux according to the present invention may or may not comprise one or more amines, preferably one or more amines. Examples of amines include N,N,N',N'-tetramethylethylenediamine, N,N,N',N'-tetraethylethylenediamine, N,N,N',N'-tetrapropylethylenediamine, N-coco-1,3-diaminopropane, 1,6-diaminohexane, 1,7-diaminoheptane, 1,8-diaminooctane, 1,9-diaminononane, and 1,10-diaminodecane, bis(2-ethylhexyl)amine, bis(2-methylhexyl)amine, diethylamine, triethylamine, cyclohexylamine, diethanolamine, triethanolamine, hydrogenated tallow alkylamines, hydrogenated (tallow alkyl) dimethylamine, and hydrogenated bis(tallow alkyl) methylamine.
[0028] As component (iv), the flux according to the invention comprises 0-20% by weight of one or more components different from components (i)-(iii), i.e. the flux according to the invention may comprise one or more components of type (iv) or may not comprise it. Examples of components of type (iv) include in particular thickeners, but may also include activators, defoamers, wetting aids and / or stabilizers. However, one advantage of the flux according to the invention, which should not be underestimated, may be that it does not necessarily require an activator, i.e. it can also be formulated without an activator.
[0029] Examples of thickening agents include ethyl cellulose, hydrogenated castor oil, glycerol-tris-12-hydroxystearin, polyamides and modified glycerol-tris-12-hydroxystearin.
[0030] Examples of low molecular weight carboxylic acids useful as activators include oxalic acid, adipic acid, malonic acid, succinic acid, glutaric acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, undecanedioic acid, dodecanedioic acid, and tridecanedioic acid. For the avoidance of doubt, the dicarboxylic acids mentioned as examples herein relate to low molecular weight carboxylic acids that are intentionally added as type (iv) components when formulating the flux according to the present invention, and should not be confused with any unintentional and unavoidable impurities in the flux according to the present invention in the form of trace amounts of carboxylic acids that are used as carboxyl building blocks in the synthesis of type (i) acidic oligoesters and are not incorporated (condensed) into the oligoesters.
[0031] Examples of halogen-containing compounds useful as activators include aniline hydrochloride, glutamic acid hydrochloride, diethanolamine hydrochloride, diethanolamine hydrobromide, triethanolamine hydrochloride, triethanolamine hydrobromide, and trans-2,3-dibromo-2-butene-1,4-diol.
[0032] The flux according to the invention is characterized by the fact that during TGA carried out in the range of 25-350 °C with the addition of synthetic air at a heating rate of 10 K / min, it undergoes a weight loss of ≥ 50% by weight when a temperature of 280 °C is reached. Synthetic air is a gas mixture of 80% by volume (volume %) nitrogen and 20% by volume oxygen. For the skilled person, it is not necessary to mention that TGA usually deals with weights of the flux according to the invention in the range of 10-30 mg. The weight loss observed in said TGA may be the result of evaporation and / or decomposition and / or oxidation. During the development of the flux according to the invention, it was found that the weight loss behavior described herein can be significantly influenced by the selection of component (i) in terms of type and amount, and in this regard the attention of the skilled person is directed in particular to the above statements regarding the type and amount of component (i). For the skilled person, useful suggestions for selecting component (i) have been given.
[0033] Preferably, the flux according to the invention, i.e. the entire flux consisting of components (i)+(ii) or (i)+(ii)+(iii) or (i)+(ii)+(iv) or (i)+(ii)+(iii)+(iv), has a flux acid number (FMSZ) in the range of 100-250 mg KOH / g, preferably in the range of 120-220 mg KOH / g. The flux acid number referred to in the present specification and in the examples can be determined according to IPC TM-650 2.3.13 (Amendment A of date 06 / 2004). The flux acid number is at least substantially or completely formed from the carboxyl groups of component (i) and the carboxyl groups optionally provided by component (iv).
[0034] The present invention provides a solder paste comprising 80-92% by weight of one or more different solders and 8-20% by weight of a flux according to the invention, i.e. a flux according to the invention in one of the above mentioned embodiments, the sum of the weight percentage of the solder according to the invention and the weight percentage of the flux being 100% by weight.
[0035] As mentioned above, the solder paste according to the invention comprises 80-92% by weight of one or more different solders, in particular a tin-based solder (a solder alloy comprising at least 80% by weight, preferably at least 83% by weight, in particular 90-99.5% by weight of tin) or a bismuth / tin-based solder (a solder alloy comprising 50-60% by weight of bismuth and 40-50% by weight of tin).
[0036] The solder preferably has a liquidus temperature in the range of 150 to 350°C, preferably in the range of 180 to 300°C.
[0037] The solder is present in the solder paste according to the invention as solder powder, as is usual for solder pastes. The ball size of the solder balls constituting the solder powder can correspond to any of the classifications according to the IPC J-STD-005A standard, i.e. the solder paste according to the invention can have solder balls of any type ball size within the type range T1 to T7.
[0038] Preferably, the solder paste according to the invention has a viscosity of 50 to 250 Pa·s. The viscosity referred to in this specification is measured at 25° C. and 10 s using a plate-plate rheometer (for example a plate-plate rheometer Physica MCR 150 from Anton-Paar) with a plate diameter of 50 mm and a measuring gap of 400 μm. -1 The shear rate can be determined using
[0039] A further object of the invention is a method for producing the solder paste according to the invention.
[0040] The method for producing a solder paste according to the present invention comprises the steps of: mixing the components of the flux according to the invention; and c) adding solder powder as described above.
[0041] The solder powder is preferably added in multiple portions, with stirring, to the prepared mixture of flux components according to the present invention, generally without heating.
[0042] The solder paste according to the present invention can be used to connect electronic components to a substrate, and it can also be used to produce solder deposits on a substrate.
[0043] When connecting an electronic component to a substrate, the contact surface of the substrate and the contact surface of the electronic component are joined via the solder paste according to the present invention.
[0044] A method of attaching an electronic component to a substrate using a solder paste according to the present invention comprises the steps of: a) providing an electronic component having a contact surface; b) providing a substrate having a contact surface; c) applying a solder paste to the contact surfaces of the electronic components and / or the contact surfaces of the substrate; d) bonding a contact surface of the electronic component to a contact surface of the substrate using solder paste; e) heating the solder paste above the liquidus temperature of the solder and then cooling the solder to solidify and form a strong bond between the electronic component and the substrate.
[0045] Steps a) and b) are self-explanatory and do not require further explanation.
[0046] In step c), the solder paste according to the invention may be applied to one or both contact surfaces by conventional methods known to those skilled in the art, such as screen or stencil printing, or dispensing or jetting.
[0047] In step d), the contact surfaces of the electronic component and the substrate can be joined together using a solder paste, i.e. a sandwich arrangement can be created from the electronic component and the substrate with the solder paste between their contact surfaces.
[0048] In step e) the sandwich assembly is soldered by heating the solder paste above the liquidus temperature of the solder, so that after cooling and solidification of the solder a robust connection is formed between the electronic component and the board via the solder paste. The solder paste is preferably heated in such a way that the solder goes into a liquid phase but does not damage the electronic component and / or the board. The sandwich assembly, and more precisely the solder paste, is preferably heated to a temperature between 5 and 60° C., preferably between 10 and 50° C., above the liquidus temperature of the solder.
[0049] Solder pastes containing the flux according to the invention are characterized by little or no void formation in the solder joints produced therefrom.As the aforementioned flux acid number of the flux according to the invention increases, in particular in the range of >120-220 mg KOH / g already mentioned as preferred, the solderability of the solder pastes containing the flux according to the invention improves in the presence of air. EXAMPLES
[0050] Example 1.1 (Preparation of an acidic oligoester from 1,4-cyclohexanedimethanol and o-phthalic acid): 100 g of 1,4-cyclohexanedimethanol and 150 g of o-phthalic acid were heated to 145° C. in a beaker with constant stirring until a clear, bubble-free composition was obtained. The resulting composition was then allowed to cool at room temperature. The acid value of the resulting oligoester was 215 mg KOH / g. Weight average molecular weight M w was 494.
[0051] Example 1.2 (Preparation of an acidic oligoester from glycerol and o-phthalic acid): 100 g of glycerol and 150 g of o-phthalic acid were heated to 145° C. in a beaker with constant stirring until a clear, bubble-free composition was obtained. The resulting composition was then allowed to cool at room temperature. The acid number of the resulting oligoester was 220 mg KOH / g. Weight average molecular weight M w was 508.
[0052] Example 1.3 (Preparation of an acidic oligoester from 2-ethyl-1,3-hexanediol and o-phthalic anhydride): 100 g of 2-ethyl-1,3-hexanediol and 150 g of o-phthalic anhydride were heated to 145° C. in a beaker with constant stirring until a clear, bubble-free composition was obtained. The resulting composition was then allowed to cool at room temperature. The acid number of the resulting oligoester was 210 mg KOH / g. Weight average molecular weight M w was 497.
[0053] Preparation of flux Each of the acidic oligoesters from Examples 1.1, 1.2 and 1.3 was dissolved in diethylene glycol monohexyl ether at 110° C. according to Table 1. The mixture was then cooled to 80° C. and the further ingredients were added and homogenized according to Table 1.
[0054] For all other fluxes, the ingredients were combined according to Table 1 and homogenized.
[0055] Preparation of solder paste To prepare the solder paste, 11 parts by weight of the flux were mixed with 89 parts by weight of solder powder (SnAgCu: 96.5 wt% Sn, 3.0 wt% Ag, 0.5 wt% Cu, type 4 according to IPC J-STD-005A standard) to form the solder paste.
[0056] Thermogravimetric analysis (TGA) of fluxes for weight loss behavior Thermogravimetric analysis was carried out using a thermobalance (TG 209 F1 Libra from Netzsch). For this purpose, a sample amount of 10.0 mg of each of the fluxes listed in Table 1 was weighed into an aluminium oxide crucible. TGA was carried out in synthetic air (80% by volume of nitrogen and 20% by volume of oxygen) in the range 25 °C to 350 °C with a heating rate of 10 K / min. The weight loss upon reaching 280 °C was recorded.
[0057] Determination of defect rates in solder joints To determine the void ratio, five printed circuit boards (carrier material: FR4 / contact surface: immersion tin) were printed with solder paste over their entire surface using a stencil printer (X5 Professional from EKRA). The thickness of the printing stencil was 120 μm. The printed circuit boards were then fitted with two MLF48-6 mm dummy components each (Amkor 48LD / MLF 6×6 mm DC Sn) using a pick-and-place machine (Siplace X2 from Siemens) and subjected to a reflow process under normal atmospheric conditions. For this purpose, the assembled printed circuit boards were passed through a reflow oven (VXS nitro 3150 type 634 from Röhm) at a speed of 76.5 cm / min with the following temperature settings: Zone 1: 150°C, Zone 2: 160°C, Zone 3: 175°C, Zone 4: 180°C, Zones 5 and 6: 200°C, Zone 7: 230°C, Zone 8: 255°C and Zone 9: 265°C.
[0058] AXI (Automated X-ray Inspection from Phoenix micromex GE PA1864) was used to evaluate the void percentage between the dummy components. For this purpose, 2D X-ray images of the solder joints were taken and the percentage of trapped gas volume was analyzed. The arithmetic mean was obtained as a percentage of the total solder joint area (contact area 4.6 mm x 4.6 mm) and the results were assigned to the following void classes: Void Class: +:<25% -:≧25~<40% --:≧40%
[0059] Testing wetting ability under normal atmospheric conditions The wetting of the solder pastes was evaluated using the melting test according to test method 2.4.45 of IPC-TM-650 (1 / 95) under normal atmospheric conditions. For this purpose, the solder paste to be tested was applied to a copper plate (20 mm x 20 mm x 0.5 mm). If the surface of the copper plate had an oxide film, it was polished with sandpaper of P600 grade to a bright metallic finish and cleaned with alcohol. If the surface of the copper plate was bright and clean, it was cleaned with alcohol only. The prepared copper plate was printed using a stencil. To do it, the template was pressed firmly against the copper plate so that the opening of the template was in the center of the copper plate. The solder paste to be tested was placed on a spatula and spread over the opening of the stencil, first with light, then with somewhat stronger pressure, until there was no more solder paste on the stencil. The stencil was then carefully peeled off, retaining the pattern defined by the stencil. The printed copper plate was placed on a first heating plate at 200° C. (i.e., set below the liquidus temperature of the solder) for 2 minutes and then immediately placed on a second heating plate at a temperature 50° C. above the liquidus temperature of the solder. After the solder paste or solder had melted, the copper plate was left on the second heating plate for an additional 5 seconds, removed and allowed to cool.
[0060] After the solder paste cooled, it was evaluated whether it melted into a spot corresponding to the size of the stencil opening or into multiple small spots, and whether the solder paste had sharp edges after melting, and whether the surface was glossy or matte.
[0061] Solder pastes were classified into four classes. Class 1: The remelted area was larger than the area previously printed with solder paste. Class 2: The remelted surface corresponded to a surface previously printed with solder paste. Class 3: The remelted area was smaller than the area previously printed with solder paste (slight solder repelling was observed). Class 4: The solder paste formed one or more solder balls and did not wet the copper plate or melt completely. [Table 1]
Claims
1. A flux, (i) 30 to 80 weight percent of one or more acidic resins; (ii) 10 to 60% by weight of at least one organic solvent; (iii) 0 to 15 wt. % of one or more amines; (iv) 0 to 20% by weight of one or more components other than components (i) to (iii); A flux characterized in that during a thermogravimetric analysis carried out in the range of 25-350°C with the addition of synthetic air at a heating rate of 10 K / min, it undergoes a weight loss of ≥ 50% by weight when a temperature of 280°C is reached.
2. 2. The flux of claim 1, wherein the one or more acidic resins are selected from the group consisting of acidic oligoesters and acidic (meth)acrylic copolymers.
3. 3. The flux according to claim 2, wherein the acidic oligoester and the acidic (meth)acrylic copolymer are each a carboxyl group-containing resin.
4. The acid oligoester has an acid number in the range of 150 to 300 mg KOH / g and a weight average molecular weight M in the range of 300 to 600. w The flux according to claim 2 or 3, having
5. The acid oligoester has an acid number in the range of 200 to 250 mg KOH / g and a weight average molecular weight M in the range of 400 to 550. w The flux of claim 4 having the formula:
6. 6. The flux of claim 2, wherein the acid oligoester is composed of one or more different low molecular weight polyols as hydroxyl building blocks and one or more different low molecular weight polycarboxylic acids as carboxyl building blocks.
7. 7. The flux of claim 2, wherein the acid oligoester is a linear acid oligoester having one or two terminal carboxyl groups, or a mixture of such oligoesters.
8. 8. The flux of claim 7, wherein the linear acidic oligoesters are composed of one or more different low molecular weight diols and one or more different low molecular weight dicarboxylic acids.
9. The acidic (meth)acrylic copolymer has an acid number in the range of 100 to 350 mg KOH / g and a weight average molecular weight M in the range of 1000 to 3500. w The flux according to any one of claims 2 to 8, having
10. The acidic (meth)acrylic copolymer has an acid number in the range of 150 to 300 mg KOH / g and a weight average molecular weight M in the range of 1000 to 3000. w 10. The flux of claim 9 having the formula:
11. 11. The flux of any one of claims 1 to 10 having a flux acid number in the range of 100 to 250 mg KOH / g.
12. A solder paste consisting of 80-92% by weight of one or more different solders and 8-20% by weight of the flux according to any one of claims 1 to 11.
13. 13. Use of the solder paste according to claim 12 for connecting an electronic component to a substrate or for producing a solder deposit on a substrate.
Citation Information
Patent Citations
Flux composition for soldering, and solder paste
JP2008100262A
Solder bump formation method
JP2012004347A
Flux and manufacturing method of electronic device
JP2016144812A
Water-soluble flux for solder paste, and solder paste
JP2016150344A
Flux and solder material
JP2020037120A